2013
DOI: 10.1160/th12-11-0793
|View full text |Cite
|
Sign up to set email alerts
|

Transient heparin-induced platelet activation linked to generation of platelet 12-lipoxygenase

Abstract: Previously we demonstrated that heparin administration during carotid endarterectomy (CEA) caused a marked, but transient increase in platelet aggregation to arachidonic acid (AA) and adenosine diphosphate (ADP), despite effective platelet cyclo-oxygenase-1 (COX-1) inhibition with aspirin. Here we investigated the metabolism of AA via platelet 12-lipoxygenase (12-LOX) as a possible mediator of the observed transient aspirin resistance, and compared the effects of unfractionated (UFH) and low-molecular-weight (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Similarly, an increased ArA cascade has been reported in platelets incubated with LDL isolated from patients having a metabolic syndrome [71]. In addition, recent studies in humans have shown that the 12-LOX pathway generating 12-HETE, but not thromboxane generation, was associated with heparin-induced platelet activation during carotid endarterectomy [72]. This reinforces the notion that the 12-HETE significance might have been previously neglected [73].…”
Section: Production and Action Of Oxygenated Pufa Derivatives In Oxidsupporting
confidence: 71%
“…Similarly, an increased ArA cascade has been reported in platelets incubated with LDL isolated from patients having a metabolic syndrome [71]. In addition, recent studies in humans have shown that the 12-LOX pathway generating 12-HETE, but not thromboxane generation, was associated with heparin-induced platelet activation during carotid endarterectomy [72]. This reinforces the notion that the 12-HETE significance might have been previously neglected [73].…”
Section: Production and Action Of Oxygenated Pufa Derivatives In Oxidsupporting
confidence: 71%
“…Heparin binds to LDL-C, VLDL, and Lp(a), and together with fibrinogen forms insoluble precipitates which are then removed by a polycarbonate membrane. Transient platelet activation accompanied by increased formation of 12-HETE due to heparin treatment has been shown previously [31]. In contrast, cascade filtration or membrane differential filtration (MDF) employs a membrane that effectively retains particles bigger than 1000 kD through which the plasma is circulated after separation of the cellular parts of the blood.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, BPC 157 by naB2 regulation could represent a mechanism to guarantee a suited transient EGR-1 activity following injury [ 39 ]. Supporting may also be the BPC 157-induced decrease of the inflammatory mediators, leukotriene B4 (LTB4), thromboxane B2 (TXB2), and myeloperoxidase (MPO), in both serum and inflamed tissue [ 40 ], largely implicated in heparin-induced platelet activation, the adhesion of leukocytes to the endothelium and concomitant increase in vascular permeability [ 41 ], prolongation of the bleeding time [ 42 ] while low-molecular-weight heparin enoxaparin causes systemic MPO activation [ 43 ]. Lastly, implicated in coagulation disorders as well as in anaphylaxis [ 44 ], in response to stimuli such inflammation and trauma, mast cells degranulate and consequently release heparin [ 45 ] while BPC 157 pretreatment significantly prevented mastocyte infiltration [ 46 ].…”
Section: Discussionmentioning
confidence: 99%